The Imperative of Self-Learning in Medicine: A Lifelong Commitment to Excellence - Lamichhane, Nirmal (Nepalese Journal of Cancer, 2025)
In conclusion, self-learning is the cornerstone of modern medical practice. It is a testament to the profession’s commitment to excellence and a reflection of the humility required to acknowledge that there is always more to learn. As the Greek philosopher Socrates aptly said, “The only true wisdom is in knowing you know nothing.” In medicine, this wisdom drives us to continually seek knowledge, not for our sake, but for the lives entrusted to our care.